PENGARUH STRES KERJA DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA KARYAWAN PADA PT BUMI MENARA INTERNUSA SURABAYA - Sri Kanti Rahayu; waras waras (Fakultas Ekonomi dan Bisnis Universita Wijaya Putra Surabaya, 2023)
This study aims to analyze the effect of work stress and work motivation on job satisfaction for employees of PT. Earth Tower Internusa Surabaya. The sample in this study were employees of PT. Earth Tower Internusa Surabaya. The sampling technique in this study using the sampling technique in this study using a non-probability sampling technique, namely purposive sampling, totaling 50 respondents. Statements were given using a questionnaire. Responses from respondents were analyzed using the Statistical Product and Service Solutions (SPSS) version 21 tool. This study uses multiple linear regression analysis. Hypothesis testing is done partially (t-test) and simultaneously (F-test). The results of this study indicate that work stress and work motivation simultaneously have a positive and significant effect on job satisfaction. Partially, work stress and work motivation have an effect on job satisfaction. The independent variables in this study have an influence of 66.7% on purchasing decisions and the rest are influenced by other variables that are not in this study.